Biaya Promosi dan Penghimpunan Dana Pihak Ketiga Pada Bank Pembiayaan Rakyat Syariah - F. Fachrunnisa (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The aim of this study is to analyze whether there is influence the expense of promotion is issued to against amount of third party assembled by BPRS. In addition, to analyze the variable lag time (lag) cost of promotion that the most effective effect on changes in third party funds obtained by BPRS. This study used regression analysis or AutoRegressive Distributed Lag (ARDL). The variables used are promotion cost as independent variable and third party fund as dependent variable. The result of this study showed that the amount of promotion cost has a positive and significant influence on the increasing amount of third party funds of BPRS, as explained by the results of ARDL analysis conducted by the author, that is change in third party funds affected by third party funds one quarter earlier and influenced by the amount of promotional costs the previous quarter or 15 months earlier. This indicates that the higher the promotion expense of budget, the BPRS will be able to collect more third party funds.